Midnight on the Marne - Adlakha, Sarah (Forge, a Tom Doherty Associates Book, 2022)
"Set during the heroism and heartbreak of World War I, and in an occupied France in an alternative timeline, Sarah Adlakha's Midnight on the Marne explores the responsibilities love lays on us and the rippling impact of our choices. France, 1918. Nurse Marcelle Fournier has important secrets to keep. Her role as a spy has made her both feared and revered, but it has also put her in extreme danger from the approaching German army. American soldier George Mountcastle feels an instant connection to the young nurse. But in times of war, love must wait. Soon, George and his best friend Philip are fighting for their lives during the Second Battle of the Marne, where George prevents Philip from a daring act that might have won the battle at the cost of his own life. On the run from a victorious Germany, George and Marcelle begin a new life with Philip and Marcelle's twin sister, Rosalie, in a brutally occupied France. Together, this self-made family navigates oppression, near starvation, and unfathomable loss, finding love and joy in unexpected moments. Years pass, and tragedy strikes, sending George on a course that could change the past and rewrite history. Playing with time is a tricky thing. If he chooses to alter history, he will surely change his own future-and perhaps not for the better"--